Asbabun Nuzul Surah Al-An’am Ayat 108 - Esa Prasastia A, Muhammad (Green Publisher, 2021)
The Koran is the mother book of Muslims which is always interesting to be discussed because various aspects of its contents can become a hot discourse. This is due to the breadth of discussion that can be drawn from it. The purpose of this study is to examine the asbabun nuzul from Surah Al-An'am verse 108. This study uses a library research method that refers to available sources both online and offline such as: scientific journals, books and news sourced from sources Trusted. This data was obtained through triangulation techniques. The data were analyzed and then conclusions were drawn. The results of this study are in the interpretation of surah al-An'am verse 108 of which it is forbidden to curse the idols of the polytheists because it is possible that the polytheists will retaliate even more badly, the curse will be addressed to Allah swt. Then from several commentators such as Jalalain's interpretation, Ibn Kathir's tafseer, and al-Misbah's interpretation also gave an explanation that education is important for every human being. And in the interpretation of the verse, the commentators when explaining the sura al-An'am verse 108 are more conspicuous in terms of preventive action, namely preventing disputes between fellow social groups.